Energy efficient refuse derived fuel (RDF) from municipal solid waste rejects: a case for Coimbatore - Kimambo, Offor N; Subramanian, P (International Journal of Environment, 2014)
In this paper production of energy efficient Refuse Derived Fuel (RDF) from municipal solid waste rejects was carried out during August 2012 – April 2013 in Coimbatore City India. Municipal Solid wastes rejects (paper, plastics with exception of polyvinyl chloride, textiles) were collected from waste dump yard of Coimbatore City. Sawdust, coir dust, water hyacinth and rice husk were mixed with the collected wastes at a fixed amount of 20 percent. After grinding, cassava starch was used as a binder to produce RDF briquettes with the help of uniaxial piston briquettes making machine. Physical, chemical and thermal characteristics of the RDF were studied to assess their potential use as energy efficient material. The analyses were divided into three categories namely, physical, proximate and ultimate analyses. Results indicated that, under physical and proximate analyses; impact resistance index (IRI) for all the RDF samples were 200, density were less than 1 kg cm-3, moisture were less than 10 % wt, ash content varied from 2.8 to 9.2 % wt, whilst volatile mater had mean value of 83.1 % wt and fixed carbon which is by subtraction ranged from 1.4 to 9.2 % wt. With respect to Ultimate analysis, Oxygen, carbon, hydrogen varied from 27.01 to 39.78 % wt, 44.8 to59.7 % wt, 5.9 to 8.1 % wt respectively. On the other hand nitrogen, sulfur and chlorine ranged from 0.18 to 0.87 % wt, 0.27 to 0.71 % wt and 0.339 to0.521 % wt respectively. Calorific values (high heating values) ranged from 5085 to 6474.9 kcal kg-1. The results were compared with Energy research Centre for the Netherland database and noted that with exception to moisture, fixed carbon and hydrogen other parameters had a significant lower or higher differences. From the study, RDF from municipal solid wastes rejects along with the additives produced high energy efficient materials. DOI: http://dx.doi.org/10.3126/ije.v3i2.10530 International Journal of the Environment Vol.3(2) 2014: 205-215